2018
DOI: 10.3390/ijerph15071324
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Molar-Incisor Hypomineralization and Dental Caries with Socioeconomic Status as an Explanatory Variable in a Group of Finnish Children

Abstract: The aim of this study was to investigate if a developmental enamel defect known as Molar-Incisor Hypomineralization (MIH) is associated with dental caries. Socioeconomic status (SES) was examined as a confounding factor between caries and MIH. In this cross-sectional study, 636 children, aged 8 to 13 years, from three towns (two rural areas and one urban area) in Finland were examined for MIH in line with the criteria of the European Academy of Paediatric Dentistry. Caries status for permanent teeth was record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
2
11
1
1
Order By: Relevance
“…In this study, caries experience had a higher prevalence when compared to MIH. e occurrence of this disease has been decreasing in recent decades, causing many Western populations to be classified as having a low caries rate; however, its control remains a challenge for many population groups [33]. e literature has shown that caries' presence negatively affects the OHRQoL of patients [2,34,35], which was also observed in this study.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, caries experience had a higher prevalence when compared to MIH. e occurrence of this disease has been decreasing in recent decades, causing many Western populations to be classified as having a low caries rate; however, its control remains a challenge for many population groups [33]. e literature has shown that caries' presence negatively affects the OHRQoL of patients [2,34,35], which was also observed in this study.…”
Section: Discussionsupporting
confidence: 75%
“…A literature review of the association of dental caries and MIH concluded that children with MIH were more likely to have dental caries in permanent teeth than were children without MIH (Americano et al, ). A study in Finland of the association between dental caries and MIH, considering locality, socioeconomic conditions, age, and MIH as predictors of dental caries, concluded that this enamel defect was the strongest indicator of dental caries in the first permanent molars (Wuollet, Laisi, Alaluusua, & Waltimo‐Sirén, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with findings that show that socioeconomic factors can make it more likely to incur caries and can themselves have an impact via spillover effects on the OHRQoL [ 26 ]. Several studies show that MIH seems to be independent of socioeconomic influence and other factors that negatively affect the OHRQoL [ 27 , 28 , 29 ]. Furthermore, untreated caries can be associated with infections, thereby indirectly leading to discomfort, pain, lack of appetite, and weight loss.…”
Section: Discussionmentioning
confidence: 99%